2022
DOI: 10.7717/peerj.12811
|View full text |Cite
|
Sign up to set email alerts
|

Defense mechanism responses to COVID-19

Abstract: The COVID-19 pandemic has had a wide range of negative physical and mental impacts. This review begins with a theoretical explanation of the psychological defense mechanisms used to deal with the pandemic. It then discusses different categories of defense mechanisms and their roles in managing the impacts of psychological distress. The aim of this review is to highlight the various psychological defense mechanisms individuals use to deal with the pandemic and to discuss how adjustment mechanisms can protect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 76 publications
(115 reference statements)
0
14
0
1
Order By: Relevance
“…The findings revealed that individuals suffering from low levels of mental health use more immature mechanisms than individuals with high levels of mental health. In general, the COVID-19 survivors tend less to use developed defense mechanisms, which can aggravate their physical state since the defense mechanisms lead to physical and psychological outcomes [15]. Therefore, when individuals use developed defensive mechanisms against bad situations, they experience less anxiety than individuals who use immature defensive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings revealed that individuals suffering from low levels of mental health use more immature mechanisms than individuals with high levels of mental health. In general, the COVID-19 survivors tend less to use developed defense mechanisms, which can aggravate their physical state since the defense mechanisms lead to physical and psychological outcomes [15]. Therefore, when individuals use developed defensive mechanisms against bad situations, they experience less anxiety than individuals who use immature defensive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it can aggravate their disease. In other words, when the patients use more immature and neurotic defensive mechanisms, their resilience decreases, and as a result, they experience more negative emotions and have fewer options to reduce their psychological distresses [15]. In general, there is a positive significant relationship between the developed defensive mechanisms and resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of mature defenses include altruism, sublimation, suppression, and humor. They serve an important role in safeguarding individuals from mental stress caused by traumatic events in their lives, like the COVID-19 epidemic (Altwaijri et al, 2022). Utilizing defensive mechanisms fosters mental resilience and has been critical in reducing psychological discomfort during the COVID-19 epidemic (Di Giuseppe et al, 2020;Walker and McCabe, 2021).…”
Section: Altruismmentioning
confidence: 99%
“…The psychological consequences and adaptability of the neurotic style may be more dependent on circumstances compared to mature and immature styles, and for this reason we focused on them in the current study. There is also evidence that neurotic defences play a critical role in mediating the psychological effects of the COVID-19 pandemic, i.e., repression allows to avoid exposure to information about the dangers of COVID-19; dissociation allows to disconnect from negative experiences, memories, thoughts, sensations, and even their identities during the pandemic; reaction formation leads to the expression of the opposite of their real feelings and emotions and displacement allows to express anger and blame family members or others for COVID-19 infection (Altwaijri et al, 2022). Neurotic defence style contributes positively to individual's psychological and social functioning (e.g.…”
Section: Introductionmentioning
confidence: 99%